Susceptibility to SARS-CoV-2 omicron following ChAdOx1 nCoV-19 and BNT162b2 versus CoronaVac vaccination - Chua, Jia Xin; Durrant, Lindy Gillian; Chok, Yin Ling; Lai, Oi Ming (Cell Press, 2022)
The emergence of SARS-CoV-2 variants raises concerns of reduced COVID-19 vaccine efficacy. We investigated the humoral immunity in uninfected and previously infected ChAdOx1 nCoV-19, BNT162b2 and CoronaVac vaccinees, who have received complete regimes of vaccines by means of a SARS-CoV-2 surrogate virus blocking test. The ChAdOx1 nCoV-19 (p = 0.0013) and BNT162b2 (p = 0.0005) vaccines induced significant higher blocking activity with longer durability against the Spike (S) protein receptor binding domain (RBD) of wild type SARS-CoV-2 than the CoronaVac vaccine in uninfected vaccinees. Prior infection improved protection in the CoronaVac vaccinees. Subsequent investigation on the breadth of SARS-CoV-2 vaccine-induced antibody blocking responses, revealed that all vaccine platforms cross-protected uninfected vaccinees against all variant of concerns, except Omicron. Prior infection protected the ChAdOx1 nCoV-19 and BNT162b2 vaccinees against Omicron but not CoronaVac vaccinees. Our study suggests that vaccines that induce broader sterilizing immunity are essential to fight against fast-emerging variants.